Design And Implementation of a Depth Stability Control System Using A Water Pressure Sensor on An Underwater Remotely Operated Vehicle (ROV) - M. Afid Afandi; Puput Wanarti Rusimamto (Department of Electrical Engineering, Faculty of Engineering, Universitas Negeri Surabaya, 2026)
This research aims to design and implement a depth control system for an Underwater ROV using the MS5837-30BA water pressure sensor, controlled by ESP8266 and STM32 microcontrollers. Data is transmitted in real time to a Ground Control Station (GCS), which also allows PID parameter configuration and joystick control. Initial testing of the sensor showed an average absolute error of 0.73 cm after adjustment. The PID control system was implemented using two approaches: MATLAB simulation and the trial-and-error method. The results show that the ROV depth control system can effectively maintain a setpoint of 50 cm below the water surface. The best performance was achieved using the trial-and-error method with PID parameters of Kp=31, Ki=0.5, and Kd=9. The system response demonstrated 0% overshoot, 0.02 cm steady-state error, 1.3 seconds rise time, and 1.6 seconds settling time. Keywords: Underwater ROV, MS5837-30BA, PID Controller, Depth Control, System Identification